Performance assessment of loRa and sigfox protocols in mobility scenarios - Oliveira, Luiz (2018)
Internet of Things (IoT) aims to offer the ability to connect common objects to the Internet providing content and information to the user, regardless of their location. Due to the wide variety of applications and the diversity of resources required to serve an application, IoT technologies are driving strong technological advancement to meet this demand, while trying to keep pace with the evolution of these applications. The characteristics required by applications, such as coverage area, scalability, transmission data rate and applicability, refer to the Medium Access Control (MAC) layer characteristics of each protocol. It is possible to compare the protocol characteristics and requirements necessary to overcome the required applications. This dissertation explores media access control layer (MAC) protocols that are used in IoT with a detailed description of such protocols grouped by short and long distance, according to their coverage radius. For short-range coverage protocols, the following are considered: Radio Frequency Identification (RFID), Near Field Communication (NFC), Bluetooth, IEEE 802.15.1, Bluetooth Low Energy, IEEE 802.15.4, Wireless-HART (Highway Addressable Remote Transducer Protocol), Z-Wave, Weightless, and IEEE 802.11 a/b/g/n/ah. For the long-distance group, Narrow Band IoT (NB-IoT), Long Term Evolution (LTE), LoRa - Long Range Coverage Protocol, and SigFox protocols are studied. For each group of protocols, a comparative study is performed considering its characteristics, limitations and behavior, in order to provide inputs and a reference study for other IoT applications. Open research issues on the topic are also identified. Within the existing protocols, the study focuses on the performance comparison of LoRa and Sigfox protocols. The study proposes qualitative and quantitative metrics to evaluate the performance of these protocols considering environments with mobility support. The study was carried out through a research methodology based on case study. To obtain the results needed for a comparative study, two real prototypes were created with an application using each technology, i.e., an application for objects monitoring location in real time. Each prototype uses a Global Positioning System (GPS) sensor to inform the point of data collection. The software was developed for the terminals operation of each protocol as well as the graphical user interfaces composing the application for better visualization of collected data. The results discussed present the behavior of the two protocols and the transmission performance according to the suggested metrics. From the obtained results it is possible to conclude the behavior of the two studied protocols do not have direct relationship among them and can present different characteristics, even though they are use simultaneously in the same environment. It is also observed the fact that transmitting at the same time did not influenced any efficiency parameter. With this, it is noticed the coexistence between them does not affect the performance of each other.